Volume 3: Coal, Biomass and Alternative Fuels; Combustion and Fuels; Oil and Gas Applications; Cycle Innovations 1991
DOI: 10.1115/91-gt-207
|View full text |Cite
|
Sign up to set email alerts
|

Motion and Evaporation of Shear-Driven Liquid Films in Turbulent Gases

Abstract: Detailed measurements of wavy liquid films driven by the shear stress of turbulent air flow are obtained for different air temperatures, air velocities and flow rates of the liquid. The experimental conditions are chosen from characteristic data of liquid film flow in prefilming airblast atomizers and film vaporization employing combustors. For the measurement of the local film thickness and film velocity a new optical instrument — based on the light absorption of the liquid — has been developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Debrégeas et al (1995) reported the thickening of viscous bursting freely suspended films by measuring the attenuation of a 0.5-mm-diameter infrared beam. Numerous similar measurements can be found elsewhere (Yang et al 2010(Yang et al , 2011Wittig et al 1992;Sattelmayer 1987) where windows were made of glass or quartz. In each case, different wavelengths have been investigated to achieve an adequate absorption coefficient according to the thickness range under investigation.…”
Section: Introductionmentioning
confidence: 59%
“…Debrégeas et al (1995) reported the thickening of viscous bursting freely suspended films by measuring the attenuation of a 0.5-mm-diameter infrared beam. Numerous similar measurements can be found elsewhere (Yang et al 2010(Yang et al , 2011Wittig et al 1992;Sattelmayer 1987) where windows were made of glass or quartz. In each case, different wavelengths have been investigated to achieve an adequate absorption coefficient according to the thickness range under investigation.…”
Section: Introductionmentioning
confidence: 59%
“…The internal passage of the hollow stator blade was connected to a water collector (15) to allow the water sucked from the blade surface to enter the water collector through the pressure difference generated by a vacuum pump (16). The exhaust steam entered a condenser (11), where it was cooled down to water and collected by a water tank.…”
Section: Experimental Facility and Proceduresmentioning
confidence: 99%
“…Wittig et al 11 reported that the water film surface velocity on a flat surface ranges from 0.5 m/s to 3.5 m/s when the main air flow velocity varies from 30 m/s to 60 m/s. The water film velocity measured by Li et al 10 ranges from 1 m/s to 4 m/s with a main air flow Mach number of 0.3.…”
Section: Flow Characteristics Of Water Film On the Blade Surfacesmentioning
confidence: 99%
“…Sattelmayer and Wittig (1986) showed that in the prefilming airblast atomizer the wavy liquid films influence the velocity of gas phase. Wittig et al (1992) found that the pre-filming flow was almost laminar, and the turbulent air or the waviness of the film didn't induce significant turbulence into the film. Brena de la Rosa (1992) inspected the effect of air swirl on the structure of a liquid spray.…”
Section: Introductionmentioning
confidence: 99%